Implementasi Manajemen Marketing Jasa Pendidikan Berbasis Media Digital di SMA Negeri 6 Kota Lubuklinggau - Khoiri, Ahmad; Supriadi, Supriadi; Siti Mukarromah (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the implementation of digital media-based educational service marketing management at SMA Negeri 6, Lubuklinggau City, to improve the school's image, promotional reach, and the effectiveness of communication with the community. The research method used was descriptive qualitative, with data collection techniques including in-depth interviews, participant observation, and documentation. The results indicate that SMA Negeri 6 has utilized social media, websites, and other digital platforms as promotional and communication tools. This strategy has been proven to increase school visibility and community participation, although challenges remain, such as limited human resources skilled in digital marketing and the suboptimal use of data analysis for campaign evaluation. The conclusion of this study is that the implementation of digital media-based marketing management at SMA Negeri 6, Lubuklinggau City, has been quite successful. However, further optimization is needed through improving the marketing team's competency and developing data-driven strategies to increase effectiveness and sustainability.   Keywords: Marketing Management, Educational Services, Digital Media, School, Institutional Image